Les modèles de répartition des revenus de type intégré : quelques éléments de comparaison - Mayer, Francine (L'Actualité économique, 1983)
AbstractThe purpose of this paper is to examine different types of models dealingwith the question of income distribution. These models can be classified into threecategories: microsimulation models, computable general equilibrium models andintegrated macro-distribution models. In this study, we are concerned with theinvestigation of a few models of each type, the analysis of their essential characteristics and the description of their comparative advantages and disadvantages.